Analytical applications of Phenylbiguanide and Phenylguanidilurea. I. Qualitative applications - Capitán, F.; Salinas, F. (Ars Pharmaceutica (Internet), 1967)
The reactivity of phenyl-biguanide and phenyl-guanidil-urea against 47 cations is being studied. Both substances, which have shown a similar behavior, as could be expected from their similar structure, have a highly selective character because they only react with the cautions Cu (II), Ni (II) and Co (II). The sensitivity of these reactions is not, in the other hand, very high, as the maximum sensitivities observed -the reactions of phenyl-guanidil-urea against Ni (II) and Co (II)- are in a ratio of 1:200.000. Futhermore, we have studied the stoichiometry of the resulting products of the reactions between phenyl-biguanide with the cations Cu (II), Ni (II) and Co (II).